BAHASA ALAY: REFLEKSI SEBUAH BUDAYA - Fahmi Gunawan (Adabiyyāt: Jurnal Bahasa dan Sastra, 2011)
Language reflects human conceptualization, human interpretation of the world. This paper aims to observe the relationship between the alay language and the alay speaker’s conceptualization/interpretation of the world. The data are taken from the written verbal interactions of  STAIN Kendari students, who are active on facebook. By using Sapir’s and Whorf’s hypothesis and qualitative descriptive method,  it  is  found that the alay language has close relationship with the alay speaker’s conceptualization/interpretation of the world. alay language style of writing which is randomized, does not have a system, is always abbreviated, and is only known by certain people, reflects the culture of indiscipline, instant, and short-sightedness.